Minimal residual disease after long-term interferon-alpha2 treatment: a report on hematological, molecular and histomorphological response patterns in 10 patients with essential thrombocythemia and polycythemia vera. Issue 2 (1st February 2016) - Utke Rank, Cecilie; Weis Bjerrum, Ole; Larsen, Thomas Stauffer; Kjær, Lasse; de Stricker, Karin; Riley, Caroline Hasselbalch; Hasselbalch, Hans Carl
Abstract : Essential thrombocythemia (ET) and polycythemia vera (PV) are Philadelphia chromosome-negative chronic myeloproliferative neoplasms (MPNs) characterized by the JAK2 V617F mutation, which can be found in more than 98% of PV patients and in ∼ 50% of ET patients. Assessment of the JAK2 V617F allele burden by a highly sensitive quantitative PCR (qPCR) assay appears to be a useful tool for monitoring minimal residual disease (MRD) and evaluating treatment efficacy. This report expands and substantiates existing data, showing that IFN-alpha2 is a highly potent immunomodulating agent capable of inducing MRD with low-burden JAK2 V617F, major molecular response (MMR), complete hematological remission (CHR) and complete histomorphological normalization of the bone marrow in a sub-set of patients with ET and PV after long-term treatment (≥ 3.5 years). Furthermore, long-lasting hematological, molecular and histomorphological remissions are sustained after discontinuation of IFN-alpha2 for up to ∼ 5–6 years.